Karakteristik Morfometrik dan Meristik Udang Air Tawar (Macrobrachium spp.) Di Perairan Sungai Ulu Ngarak, Kabupaten Landak - Listia, M Windi; Munir, Ahmad Mulyadi Sirodjul (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2025)
The Ulu Ngarak River is one of the rivers located in Ngarak Village, Mandor District, Landak Regency. The riverbed consists of muddy, slightly sandy, and large rocky substrates, with depths ranging from 30 cm to 120 cm. The presence of various freshwater shrimp species in a river can serve as an indicator of water quality and contribute to improving the environmental conditions of the aquatic ecosystem. This study aims to identify the freshwater shrimp species found in the Ulu Ngarak River, Landak Regency, based on their morphometric and meristic characteristics and to analyze the river's environmental conditions. The research employed a purposive sampling method with three sampling stations. Morphometric identification was conducted by measuring different body parts of the shrimp, while meristic characteristics were analyzed based on the countable features of their body structures. The study identified a total of 462 freshwater shrimp individuals (Macrobrachium spp.), consisting of four species: Macrobrachium malayanum, Macrobrachium sintangense, Macrobrachium lar, and Macrobrachium lanchesteri. Morphometric analysis revealed variations in body size among species, while meristic analysis showed differences in telson spine count, body weight, number of dorsal and ventral teeth, and the number of walking and swimming legs. Environmental parameter analysis indicated that temperature, pH, dissolved oxygen, and water current velocity were within a range that supports the survival of freshwater shrimp. This study provides essential baseline information that can be utilized for the management and conservation of freshwater shrimp populations in the Ulu Ngarak River.